METODE LOGIKA FUZZY SEBAGAI EVALUASI DISTRIBUSI DAYA LISTRIK BERDASARKAN BEBAN PUNCAK PEMBANGKIT TENAGA LISTRIK - Fifi D. Rosalina; Yuniar Farida; Abdulloh Hamid (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2016)
Evaluation of peak load on the power system is raised very influential on the development of electric power availability in the various provinces. By reviewing the peak load for a year, can be implemented for the evaluation of power generation as a simulation of the electrical energy supply for the future. Evaluating the peak load also depends on several factors such as installed capacity, power capacity, and production at some plants systems. It can be the control of the forces generated on each such PLTA, PLTU, PLTG, and PLTS. Fuzzy logic method is an effective method that can be applied to evaluate peak loads with high accuracy. Thus the fulfillment of the electricity will be met with the desired reliability level. The evaluation of the resulting output can be used as a control for the security of the power system. With the results obtained is the highest error rate reached 60%, and has done training and testing data is as much as 4x to test the parameters of the membership function has been determined by the highest recognize result of 12.5%